HUBUNGAN ANTARA KEMAMPUAN KOGNITIF DENGAN UNJUK KERJA SISWA KELAS VIII SMP N 1 BANAWA SELATAN - Aprilianti, Asti; Muslimin, Muslimin (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
This study aims to determine the magnitude of the relationship between cognitive abilities and student performance at SMP Negeri 1 Banawa Selatan in the Academic Year 2021/2022. This research is quantitative research, the method used is the correlation method. The population in this study was all class VIII SMP N 1 Banawa Selatan Academic Year 2021/2022 with a total population of 85 students, with a sample of 43 students. The instrument used was a cognitive ability essay test with 24 questions and a student performance test with 10 questions. The results of the prerequisite test results of the research are the cognitive abilities and performance of students with normal and linear distributions and based on the regression feasibility test, it shows that all data are eligible for regression testing. The results of the regression and determination tests obtained significant values. Based on the results of the research analysis, it can be concluded that the relationship between cognitive abilities and student performance is significant. The magnitude of the effect of cognitive ability on performance is 52.9% seen in the coefficient of determination.